Physiotherapists' perceptions of learning and implementing a biopsychosocial intervention to treat musculoskeletal pain conditions: a systematic review and metasynthesis of qualitative studies. Issue 6 (June 2020) - Holopainen, Riikka; Simpson, Phoebe; Piirainen, Arja; Karppinen, Jaro; Schütze, Rob; Smith, Anne; O'Sullivan, Peter; Kent, Peter
Abstract : Abstract: Clinical practice guidelines recommend a biopsychosocial approach for the management of musculoskeletal pain conditions, but physiotherapists have reported feeling inadequately trained and lacking in confidence to deal with psychosocial issues. Although a growing number of studies are exploring physiotherapists' perceptions of biopsychosocial training, the results have not been synthesized. Therefore, the aim of this systematic review and metasynthesis of qualitative studies was to explore physiotherapists' perceptions of learning and implementing a biopsychosocial intervention to treat musculoskeletal pain conditions. A search of the electronic databases: MEDLINE, EMBASE, CINAHL, ERIC, PsycInfo, SportDiscus, and Sociological abstracts identified eligible studies. We included full-text qualitative and mixed-methodology studies published in English, which investigated physiotherapists' perceptions of learning and implementing biopsychosocial interventions. Twelve studies involving 113 participants met the inclusion criteria, and a thematic synthesis was conducted. The quality of the included studies was appraised using the Clinical Appraisal Screening Program. Four main themes emerged from the data: changed understanding and practice, professional benefits, clinical challenges, and learning requirements. The results of this study indicate that although the physiotherapists reported a shift towards more biopsychosocial and person-centered approaches, the training interventions did not sufficiently help them feel confident in delivering all the aspects. Planning future implementation interventions and training physiotherapists through a biopsychosocial approach should focus on adequate training and individualized mentoring related to psychosocial factors, and discussion of role boundaries, patient expectations, and organizational factors such as time constraints and referral pathways. Abstract : Supplemental Digital Content is Available in the Text.